An interpretive structural modeling (ISM) and decision-making trail and evaluation laboratory (DEMATEL) method approach for the analysis of barriers of waste recycling in India. (1st February 2018) - Chauhan, Ankur; Singh, Amol; Jharkharia, Sanjay
ABSTRACT: Increasing amount of wastes is posing great difficulties for all countries across the world. The problem of waste management is more severe in developing countries such as India where the rates of economic growth and urbanization are increasing at a fast pace. The governments in these countries are often constrained by limited technical and financial capabilities, which prevent them from effectively addressing these problems. There is a limited participation from the private players too in terms of setting up of waste recycling units. The present study aims at identifying various barriers that challenge the establishment of these units, specific to India. Further, it attempts to identify the most influential barriers by utilizing multicriterion decision-making tools of interpretive structural modeling (ISM) and decision-making trail and evaluation laboratory (DEMATEL). The findings of the study suggest that the lack of funds, input material, and subsidy are the most influential barriers that are needed to be addressed for the development of waste recycling infrastructure in India. Implications : This work has been carried out to address the problem of proper waste management in India. To deal with this problem, the method of waste recycling has been felt appropriate by the government of various countries, including India. Therefore, the barriers that play vital role in waste recycling for private players have been identified and their importance has been established with the help of ISM and DEMATEL methods. Doing so will assist the government to take appropriate steps for the betterment of waste recycling infrastructure in India and enhance waste management.